Zoledronic acid in combination with serine/threonine phosphatase inhibitors induces enhanced cytotoxicity and apoptosis in hormone‐refractory prostate cancer cell lines by decreasing the activities of PP1 and PP2A - Cirak, Yalcin; Varol, Umut; Atmaca, Harika; Kisim, Asli; Sezgin, Canfeza; Karabulut, Bulent; Uzunoglu, Selim; Uslu, Ruchan; Karaca, Burcak (BJU international, 2012)
What's known on the subject? and What does the study add? Prostate cancer is the second most common cancer diagnosed among elderly men. Current standard of care with surgery, chemotherapy or radiation in prostate cancer patients are of limited efficacy, especially in the androgen refractory state of the disease, and unfortunately metastatic disease remains incurable. Skeletal metastases are the most common site for metastases for prostate cancer and bisphosphonates have been widely used for the treatment of morbidity due to skeletal related events. Zoledronic acid (ZA) is the most potent member of the nitrogen containing new generation bisphosphonate (N‐BPs) family. Okadaic acid (OA) and Calyculin A (CA) are the most commonly used inhibitors of PP1 and 2A. OA, extracted from common black sponge Halachondria okaddai is a potent inhibitor of protein phosphatases, PP1 and PP2A, and CA was isolated from another marine sponge, Discodermia calyx. Therapies based on combinations of chemotherapeutics with phosphatase inhibitors that target signaling pathways within the cell with different mechanisms of action, may be useful for increasing therapeutic effect and also diminish toxic side effects by decreasing the doses of conventional chemotherapeutics. Although clinically well known, the in vitro effects of ZA on cancer cells and the underlying mechanisms are not well elucidated. In our previous studies, we have already shown anticancer effect of ZA in hormone‐and drug refractory prostate cancer cells, PC‐3 and DU‐145. In addition to this, we have also shown that this anticancer effect may be augmented with some cytotoxic agents in prostate cancer. Now, in our present study, we have investigated whether ZA induced growth inhibition and apoptosis in PC‐3 and DU‐145 may be enhanced by the combination with CA or OA, through inhibition of serine/threonine phosphatases in prostate cancer cells. Both ZA/CA and ZA/OA combinations inhibited the cell viability of hormone‐and drug refractory prostate cancer cells at in vivo achievable therapeutic concentrations. Moreover, a potentiation of the apoptotic effects of the combinations was also observed in the same experimental conditions. This is the first report of a synergistic combination of ZA with phosphatase inhibitors CA and OA which inhibits cell viability and induces apoptosis in human hormone and drug refractory prostate cancer cells. OBJECTIVES • To investigate if the cytotoxic and apoptotic effect of zoledronic acid (ZA) can be enhanced by the addition of the serine/threonine protein phosphatase inhibitors calyculin A (CA) and okadaic acid (OA) in hormone and drug refractory prostate cancer cells, PC‐3 and DU‐145. • To discover the effect of these combination treatments on phosphatase 1 (PP1) and PP2A protein expression levels in prostate cancer cells. MATERIALS AND METHODS • An XTT cell viability assay was used to determine cytotoxicity. • Apoptosis was evaluated by enzyme‐linked immunosorbent assay (ELISA) using a Cell Death Detection ELISA Plus Kit and verified by measuring caspase 3/7 enzyme activity. • The PP1 and PP2A enzyme activities were evaluated by serine/threonine phosphatase ELISA and expression levels of PP1 and PP2A proteins were then re‐assessed by Western blot analysis. RESULTS • Combination of ZA with either CA or OA showed synergistic cytotoxicity and apoptosis compared with any agent alone in both PC‐3 and DU‐145 prostate cancer cells. • The combination of ZA with phosphatase inhibitors resulted in enhanced suppression of both PP1 and PP2A enzyme activity and protein levels, which was more overt with the ZA/CA combination. CONCLUSION • Results from our study increase the translational potential of our in vitro findings and offer the basic rationale for the design of new combinatory strategies with ZA and phosphatase inhibitors for the treatment of prostate cancer, which may become resistant to conventional therapy.